Cooperation between learning venues and its limits: The hotel industry in Cancún (Mexico) - Beke Vogelsang; Natascha Röhrer; Martina Fuchs; Matthias Pilz (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Purpose: Recently, high-quality vocational education and training has attracted much attention in Mexico. In this context, more practically applied skills are taught 'on a dual basis', combining classroom-based training with practical, on the job, training within the company. Dual practices are expected to modernize the skills formation system, and simultaneously support companies, while ensuring provision of skilled workers. For this reason, the vocational training system has been reformed in recent years. Hence, it is necessary that schools and universities, as well as companies, closely interact and coordinate their activities. It is also important that there is successful cooperation between vocational training organizations and companies, to contribute to the modernization of vocational training. The aim of this paper is to examine the cooperation between learning venues of vocational education in the hotel industry in Cancún (Quintana Roo, Mexico), one of the most important tourism destinations in Latin America. Research in vocational education and training, reveals a particular focus on the principles that are necessary for successful cooperation between learning venues. This study examines whether the setting of common goals, communication between companies and training organizations and governance are equally important. Methods: In an exploratory approach, based on a qualitative framework, ten face-to-face expert interviews were conducted in Cancún. The interviews were then fully transcribed and evaluated using qualitative methods. The survey is complemented by further document analysis. Findings: The results show that for successful cooperation between learning venues, the coordination of a common goal (to secure the availability of skilled workers) between different actors, and communication between companies and vocational training organizations, are particularly important for successful cooperation. Furthermore, it seems that companies are taking on a more dominant role, so that vocational training organizations must be more in line with the wishes of the hotels. The results indicate that partnership-based action is not very obvious. Accordingly, the aspect of governance plays a subordinate role. Conclusion: The study shows that cooperation between learning venues in other regions and industries, requires certain principles to be successful. In this respect, the duration of the relationship as well as the specificity of a region or sector can influence the required principles. Therefore, the cooperation partners should agree on the principles in advance.
Keywords: 330; Tourism; Hotel Industry; Cooperation Between Learning Venues; Limits; Mexico; VET; Vocational Education and Training